2001
DOI: 10.1007/s001980070027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Six Calcaneal Quantitative Ultrasound Devices: Precision and Hip Fracture Discrimination

Abstract: Quantitative ultrasound (QUS) is now accepted as a useful tool in the management of osteoporosis. There are a variety of QUS devices clinically available with a number of differences among them, including their coupling methods, parameter calculation algorithms and sites of measurement. This study evaluated the abilities of six calcaneal QUS devices to discriminate between normal and hip-fractured subjects compared with the established method of dual-energy X-ray absorptiometry (DXA). The short-term and mid-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
2
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(89 citation statements)
references
References 57 publications
5
77
2
5
Order By: Relevance
“…This range of speeds of sound is similar to the range seen in clinical measurements of the speed of sound in the calcaneus based on analysis of the unseparated wave. 23,24 The difference between the fast and the slow wave speeds is smaller in this study than in other studies that have reported the speed of sound for both waves. 7,16,[25][26][27] This result is expected because the fast and slow wave speeds are most similar when propagating perpendicular to the predominant fiber direction.…”
Section: A Phase Velocitycontrasting
confidence: 74%
“…This range of speeds of sound is similar to the range seen in clinical measurements of the speed of sound in the calcaneus based on analysis of the unseparated wave. 23,24 The difference between the fast and the slow wave speeds is smaller in this study than in other studies that have reported the speed of sound for both waves. 7,16,[25][26][27] This result is expected because the fast and slow wave speeds are most similar when propagating perpendicular to the predominant fiber direction.…”
Section: A Phase Velocitycontrasting
confidence: 74%
“…However, it is possible that positioning errors are not a major source of error in gelcoupled devices. One could speculate that because gel-coupled devices have consistently performed poorly compared with water-coupled devices, 9 issues of coupling (time of gel application and type of gel), the presence of edema, 22 and bonding of the transducers 23 may contribute significantly to the level of precision. Because gel-coupled devices are relatively portable, it is essential to identify the causes of poor precision.…”
Section: Measurement Precisionmentioning
confidence: 99%
“…Utilizamos as referências do aparelho fornecidas pelo fabricante baseado em estudo brasileiro que demonstrou a similaridade entre as duas curvas de referência 12 , conferindo para o mesmo um bom grau de confiabilidade. A existência de estudos equiparando múltiplas máquinas de ultra-sonometria óssea utilizando gel ou água 37,38,39,40 , e do estudo de Rodrigues et al 41 demonstrando a boa correlação entre Sonost 2000 e a resistência óssea em humanos, nos permitem ter uma relativa segurança com o seu uso.…”
Section: Discussionunclassified